2021
DOI: 10.19088/apra.2021.012
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19 Pandemic and Household Rice Consumption Patterns in Ethiopia: The Case of Addis Ababa

Abstract: The outbreak of COVID-19 also resulted in moderate changes to the operation of the domestic rice value chain in Ethiopia. These were caused by changing responses of value chain actors (domestic and others engaged in rice imports) to the COVID-19 prevention measures put in place by the government. These changes increased the price of rice, which favoured rice producers and adversely affected urban consumers. This research note assesses household rice consumption patterns in Addis Ababa by comparing the situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The study's findings indicated that the components of logistics service quality include personal contact quality, order release quantities, information quality, ordering procedures, order accuracy, order condition, order quality, order discrepancy handling, and timeliness. Alemu (2016) proposed that service quality includes: information quality, order procedure, timeliness, order condition, order accuracy, order discrepancy handling, and personal contact quality. Besides, according to Thai (2008), social responsibility is an important aspect that can promote or hinder the image or reputation of a business and services quality.…”
Section: Logistics Quality Servicesmentioning
confidence: 99%
“…The study's findings indicated that the components of logistics service quality include personal contact quality, order release quantities, information quality, ordering procedures, order accuracy, order condition, order quality, order discrepancy handling, and timeliness. Alemu (2016) proposed that service quality includes: information quality, order procedure, timeliness, order condition, order accuracy, order discrepancy handling, and personal contact quality. Besides, according to Thai (2008), social responsibility is an important aspect that can promote or hinder the image or reputation of a business and services quality.…”
Section: Logistics Quality Servicesmentioning
confidence: 99%
“…For Amharic, Mehamed (2019) conducted the NER experiment on a corpus of 10,405 tokens using the CRF classifier. Alemu (2013) conducted the experiments on a manually developed corpus of 13,538 words with the Stanford tagging scheme. Tadele (2014) used a hybrid of machine learning (decision trees and support vector machines) and rule-based methods.…”
Section: Named Entity Recognition (Ner)mentioning
confidence: 99%